POLITIK HUKUM PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM (Studi Putusan Nomor 2/PDT/2021/PT TJK.) - Muhamad Ibnu Afif; Gunawan Djajaputra (Jurnal Hukum Adigama, 2022)
The purpose of this research is to get more knowledge about the causes of land rights conflicts and possible solutions. According to a method of normative legal analysis, conflicts over land rights are settled by administrative procedures provided by government organizations, in this instance the National Land Agency. After the 1960s BAL went into effect, a number of laws were created in an effort to prevent future hiccups in the decision-making process over how to utilize the land. The BPN Agrarian Directorate further acts as a place for mediation if there are conflicts so that the parties engaged in a land ownership issue may reach a peaceful conclusion. I In the event that land ownership disputes cannot be settled with the assistance of the government, the General Court, the Arbitration Board, and the Directorate of Agrarian Affairs shall all serve as a bridge for the disputing parties to obtain legal clarity on the status of the disputed property. The available choices for handling disputes may be able to balance maintaining the objectives and clarity of the law with the needs of the disputing parties.